The Influence of Imagery Training and Self-Confidence on Futsal Shooting Results in Extracurricular Students at SMA Negeri in Bengkulu City - Angga Febrinaldo; Wilda Welis; Donie; Nurul Ihsan (UNIB Press, 2023)
The purpose of this study was to determine: (I) the difference in the effect of internal imagery and external imagery on shooting results, (2) the difference in the effect of high self-confidence and low self-confidence on shooting results, and (3) the interaction between imagery training and self-confidence on shooting results. This study uses a 2x2 factorial design experimental method. The population of the study was the participants in the futsal extracurricular activities at State Senior High Schools in Bengkulu City. The sample of this research was determined by random sampling technique which amounted to three schools namely SMAN 7 Bengkulu, SMAN 10 Bengkulu, SMAN 11 Bengkulu with a total of 42 students. The instrument measures the level of self-confidence using a self-confidence questionnaire and measures the results of the penalty kick shooting accuracy test using the Brace shooting penalty kick test. Data analysis used two-way analysis of variance (ANOVA) at a significant level of a = 0.05. The results of the study are as follows: (1) There is a significant difference in effect between internal imagery training and external imagery training on futsal shooting results, (2) There is a difference in effect between high self-confidence and low self-confidence on futsal shooting results, (3) There is an interaction between imagery training and self-confidence from futsal shooting results.